THE EFFECTIVENESS OF WAKELET TOWARD EIGHTH GRADE STUDENTS’ VOCABULARY MASTERY AT SMP YOS SUDARSO METRO - Yoja Exgysta; Dedy Subandowo; Fenny Thresia (English Education Study Program, 2026)
This study investigated the effect of Wakelet on eighth-grade students' vocabulary mastery at SMP Yos Sudarso Metro using a quasi-experimental design with a pre-test and post-test administered to experimental and control groups. The experimental group (n=30) received vocabulary instruction using Wakelet, while the control group (n=30) was taught using conventional methods. The findings from the Paired Sample T-Test indicated a significant improvement in vocabulary mastery within the experimental group (p < 0.001). However, the Independent Sample T-Test revealed no statistically significant difference in post-test scores between the experimental and control groups (p = 0.504). The study concludes that while Wakelet demonstrates a positive effect on vocabulary mastery, it does not provide significantly different results compared to traditional teaching methods. The findings suggest that combining Wakelet with traditional teaching methods can improve vocabulary learning. Future research is recommended to examine the long-term impact of using the Wakelet and the potential for developing other language skills.